Clinical evaluation of the effectiveness of the treatment of chronic forms of periodontitis using transchannel laser non-pigmented photoablation - N. A. Chunikhin; I. O. Sorokin; I. V. Zima; E. A. Bazikyan; A. A. Chunikhin (Эндодонтия Today, 2023)
Aim. Comparative evaluation of the effectiveness of the treatment of chronic forms of periodontitis using a new technology of transcanal laser pigmentless photoablation and classical classical surgical techniques for the treatment of periapical lesions with odonto-preserving operations.  Materials and methods. The treatment was carried out in 40 patients with chronic periodontitis on 64 teeth. All patients were divided into 2 groups – the main group and comparison of 20 in each. In the main group, treatment was carried out with the use of transchannel laser photoablation, in the comparison group, with the use of surgical odonto-preserving techniques. The immediate and long-term results of treatment were evaluated according to clinical and radiological signs. Results. In the main group using the new technology of laser transcanal photoablation on the 3rd day, patients noted the presence of pain 3.3 times less, the presence of hyperemia 6.4 times less, the presence of edema 5.3 times less than in the comparison group with the use of traditional surgical procedures. treatment methods. X-ray 12 months after treatment in the main group, complete recovery was observed 1.46 times in more cases than in the control group.  Conclusions. Our clinical and radiological studies confirm the expediency of using transchannel laser photoablation in the treatment of chronic periodontitis.